MICROWAVE-ASSISTED SYNTHESIS OF LISICON STRUCTURED LI3V2(PO4)3/ GRAPHENE COMPOSITE - Mukushev, Ilyas; Nurpeissova, Arailym; Kalimuldina, Gulnur; Bakenov, Zhumabay (National Laboratory Astana, 2022)
One of the main challenges in cathodes at low temperatures (LT) is associated with low electronic and ionic conductivity. Graphene can be used to increase electronic conductivity, but most of the experimental methods for graphene composites require long-term high-temperature treatment and an inert atmosphere, which causes high energy consumption and cost increase. In comparison, microwave heating can simplify the reduction step of graphene oxide and provide a convenient, economical, and effective method of preparing graphene composites. LISICON structured Li3V2(PO4)3 (r-LVP) was reported to have enhanced LT performance due to high alkali- ion mobility and rhombohedral structure with the open framework.
Keywords: Type of access: Embargo; graphene